“if we don’t regroup, hunger will kill us…”: a qualitative study on measures of physical distancing during covid-19 among internally displaced persons in Burkina Faso - Kadio, Kadidiatou; Ly, Antarou; Ouédraogo, Adidjata; Ahmed, Mohamed Ali Ag; Yaya, Sanni; Gagnon, Marie-Pierre (Frontiers in Sociology, 2023)
This study contributes to the body of knowledge on IDPs in the context of security crisis related to terrorism. Very little research has been done on covid-19 amongst IDPs in Africa and this is one of the first studies in Burkina Faso. Our diversified sample allowed us to consider the discourses of humanitarian actors working with IDPs, but also the discourses of IDPs in a context of aggravated health and security crisis. The challenges encountered by IDPs in implementing physical distancing and the coping strategies have been documented. It showed some possible solutions that decision-makers could use in order to facilitate the appropriation of this measure by IDPs. This is a contribution to the field of applied human and social science research They will help to anticipate solutions in the event of a resurgence of covid-19 cases. In the current context, where the spread of the disease seems to be under control, concerted action should now be taken in the event of the detection of a case of covid-19 in the various IDP sites.